UPAYA PENINGKATAN HASIL BELAJAR PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Kurnaedi (UNISAN JURNAL, 2024)
The point of this examination is to decide endeavors to further develop learning results in Islamic strict schooling subjects. There are a few learning techniques that can be utilized as instructing and learning systems for Islamic Strict Training subjects. This methodology is tracked down in the idea or configuration (plan) position contained in the learning execution plan. This strategy is at a pragmatic level where plans can be acknowledged utilizing the technique picked by the educator. From this depiction it tends to be presumed that there are a few techniques that can be utilized as instructing and learning systems for Islamic Strict Training subjects, for example, giving model models, offering guidance, acclimation, talks, questions and replies, conversations, and verification.